Potential Role of Native Arbuscular Mycorrhizal Fungi (AMF) in the Restoration of Laurisilva - Melo Drumonde, Catarina (2020)
The beneficial association of seedlings with arbuscular mycorrhizal fungi (AMF) is thought to improve early tree establishment through increased uptake of poorly labile soil nutrients (particularly P) and enhancing plant tolerance to biotic and abiotic factors. Seedlings of Juniperus brevifolia, an endemic woody plant of the Azores archipelago with potential commercial value, was grown in the nursery with and without inoculation by a commercial plant growth promoter consisting of AMF isolated from the Azores (MICOazorica). Treatments were arranged in a randomized complete block design in a greenhouse. At six months after planting, all AMF-inoculated plants were colonized. The percentage of colonization varied between 46% and 96% (Mean 70%). At harvest, all physical parameters were significantly greater in AMF-inoculated plants relative to uninoculated plants. Based on the obtained results, we strongly advise the use of native AMF, in strategies used in restoration programs in the Azores.